Minimal-Access Left Ventricular Assist Device Implantation. Issue 4 (July 2014) - Cheung, Anson; Soon, Jia-Lin; Bashir, Jamil; Kaan, Annemarie; Ignaszewski, Andrew
Objective: The left ventricular assist device (LVAD) is typically implanted through a full sternotomy on cardiopulmonary bypass (CPB). Minimally invasive surgery (MIS) modifications include multiple smaller incisions, using "virgin" territory, and minimized CPB time. Methods: Forty-two LVAD implantations were retrospectively reviewed. Twenty-five minimally invasive implantations (MIS, 20 HeartMate II and 5 HeartWare) were compared with 17 sternotomy implantations (12 HeartMate II and 5 HeartWare). The choice of MIS incisions was device dependent: (1) three separate incisions for the HeartMate II or (2) two incisions for the HeartWare device. Four HeartWare LVADs were implanted off-pump (three using the MIS approach). Results: The median patient age was 52 years (range, 18–69 years). Overall survival was 81% at a mean (SD) follow-up of 495 (375) days. Thirty-day mortality was 9.5% (one MIS and three sternotomy patients). Five patients (11.9%) died while on LVAD, 18 (42.9%) underwent transplantation, 6 (14.3%) underwent weaning and explantation, and 13 (31.0%) remained on support. Preoperative ventilatory and circulatory supports were more common in the sternotomy group. The MIS patients had shorter CPB time [51.4 (34.9) vs 83.6 (40.4) minutes, P = 0.014] and showed a trend toward lower red blood cell and platelet transfusion requirement. The durations of hospitalization, inotropic support, intensive care unit stay, and LVAD support were not significantly different. Conclusions: Minimally invasive surgery LVAD implantation is feasible. The shorter CPB duration and off-pump approach may be advantageous. Avoiding sternotomy may also reduce adhesions encountered during subsequent cardiac transplantation.